Alternative futures for the Pacific food system - Secretariat of the Pacific Community (2015)
The food system of the Pacific region is undergoing profound changes that will be felt for generations. The main pillars of food security – availability, access, and consumption of nutritious food – are being challenged by rapid population growth and urbanisation, shortages of arable land, and cheap, nutritionally poor food imports from burgeoning global trade. As a result, many Pacific Island countries and territories are now dependent on imported food, and the incidence of non-communicable diseases (NCDs) is among the highest in the world.